A soft neural interface with a tapered peristaltic micropump for wireless drug delivery - Hyeokjun Lee; Soojeong Song; Jeongdae Ha; Yoon Kyeung Lee; Kyung-In Jang (npj Flexible Electronics)
Abstract Achieving precise, localized drug delivery within the brain remains a major challenge due to the restrictive nature of the blood–brain barrier and the risk of systemic toxicity. Here, we present a fully soft neural interface incorporating a thermo-pneumatic peristaltic micropump integrated with asymmetrically tapered microchannels for targeted, on-demand wireless drug delivery. All structural and functional components are fabricated from soft materials, ensuring mechanical compatibility with brain tissue. The system employs sequential actuation of microheaters to generate unidirectional airflow that drives drug infusion from an on-board reservoir. The nozzle–diffuser geometry of the microchannels minimizes backflow while enabling controlled, continuous delivery without mechanical valves. Fluid dynamics simulations guided the optimization of the microfluidic design, resulting in robust forward flow with minimal reflux. Benchtop validation in brain-mimicking phantoms confirmed consistent and programmable drug infusion. This platform represents a significant advancement in neuropharmacological research and therapeutic delivery for central nervous system disorders.